Developing web‐based Triple P 'Positive Parenting Programme' for families of children with asthma. Issue 4 (12th May 2013) - Clarke, S.‐A.; Calam, R.; Morawska, A.; Sanders, M.
Abstract Background We examined the feasibility of self‐directed Triple P 'Positive Parenting Programme' for optimizing parents' management of childhood asthma and behaviour. Methods Eligible families were invited to access asthma‐specific web‐based Triple P as part of a preliminary randomized controlled study. Results Initial study information and introductory website pages received considerable interest but intervention uptake was poor with high rates of attrition. Conclusions Although parents of children with asthma show willingness to access web‐based parenting support, further work is necessary to develop engaging websites and determine barriers to uptake, and adherence to online parenting interventions with this population.